Inocentes en Quito: A party for all citizen in Quito (First half of the XX century): Inocentes en Quito: Una fiesta para toda la ciudad (Primera mitad del siglo XX) - Checa Ron, Sophia (2015)
From 28 December to 6 January was to hold in Quito the “Fiesta de Inocentes”. There were ten days when the whole city used to be carried by the great sense of humor and happiness, and its citizens did not doubt to participate in public and private activities, among which mask dances and the flowers parades were the highlight of these festivities. The mask dances were held in squares, theaters, ball rooms, hotels, private houses, etc. while the flower parades which constitute the end of the festivities were done on streets and balconies, these stages served for special battles with flowers and paper ribbons. The main characters of this feast were people in disguises, men and women of every age and social conditions were worn typical and foreign dresses or fantasy customs creating a cheerful environment, which capture the attention of the audience that expressed the ingenuity of people from Quito.